Kesadaran Nazir Wakaf atas Legalitas Tanah Wakaf Ditinjau dari Undang-Undang Nomor 41 Tahun 2004: Studi Kasus KUA Kecamatan Tanjung Beringin - M. Farhan Hidayat; Syaiful Amri (CV Global Research Publication, 2026)
This study was motivated by a research gap between the regulations on waqf in Law No. 41 of 2004 and actual practices in the field, particularly regarding the low level of awareness among waqf trustees regarding the legality of waqf land at the local level. This study aims to analyze the legal awareness of waqf trustees, focusing on the administrative legality of waqf. The research design employs a qualitative approach using a case study at the KUA of Tanjung Beringin Subdistrict. The methodology utilized is in-depth interviews, employing purposive sampling of relevant waqf trustees and KUA staff. The research results indicate that nazirs’ understanding remains limited to ritual aspects and does not yet encompass formal legalities such as the Wakaf Declaration Deed and land certification. The significance of the findings lies in the relationship between low legal understanding and weak protection and management of wakaf. The contribution of this study is to provide empirical evidence regarding the importance of improving nazir legal literacy. The implication is that there is a need to strengthen outreach, enhance the capacity of nazirs, and optimize the roles of the KUA and related institutions to achieve legal, professional, and sustainable waqf management.